Optimizing carbon emission analysis for sustainable environmental impact / Nazatul Adibah Tham Iskandar Nasruddin Tham - Iskandar Nasruddin Tham, Nazatul Adibah Tham (2024)
This project aims to tackle the accessibility and cost challenges associated with carbon emission analysis tools by developing a user-friendly application system. The objectives are to democratize carbon emission calculations and optimize emission values using advanced swarm-based algorithms. The methodology includes designing an accessible application, performing a comprehensive carbon emission analysis for Engineering Tower 2 in accordance with GHG Protocol and ISO 14064 guidelines, and incorporating participation factors and utilization indices to refine emission values. The findings demonstrate that the application significantly reduces barriers to accurate emission assessments, and the detailed analysis highlights key areas for improvement in the carbon footprint of Engineering Tower 2. The optimization techniques enhance the precision and efficiency of emission reduction efforts. In conclusion, this project provides an effective and accessible tool for carbon management, promoting sustainable practices and contributing to global climate change mitigation efforts.